The Reading and Writing Algorithmic “Revolution”: Exploring Wattpad's Story DNA Machine Learning and the Production and Consumption of Young Adult Fiction - Emilia Oriana Pozzoni (Estudios de Teoría Literaria, 2023)
This paper takes as its starting point the current debates surrounding new forms of reading and writing on online platforms, particularly those interfaces aimed at adolescent or young adult audiences. The focal point of this analysis is Wattpad, a digital literary production, distribution, and consumption platform that presents reading and writing as a communal, multimedia, and interactive phenomenon. This article outlines some of its key features, along with a brief data analysis aiming to sketch the general functioning of the algorithm that determines the success of texts published on the platform. By creating two databases using web scraping techniques and subsequently processing them using Python in the Jupyter Notebooks environment, this study draws partial conclusions about the potential of the website and some of its potential transformations in young adult reading and writing practices.